Nutraceuticals as Potential Targets for the Development of a Functional Beverage for Improving Sleep Quality - Amanda Bulman; Nathan M. D’Cunha; Wolfgang Marx; Andrew J. McKune; Rati Jani; Nenad Naumovski (Beverages, 2021)
Functional beverages can be a valuable component of the human diet with the ability to not only provide essential hydration but to deliver important bioactive compounds that can contribute to chronic disease treatment and prevention. One area of the functional beverage market that has seen an increase in demand in recent years are beverages that promote relaxation and sleep. Sleep is an essential biological process, with optimal sleep being defined as one of adequate duration, quality and timing. It is regulated by a number of neurotransmitters which are, in turn, regulated by dietary intake of essential bioactive compounds. This narrative review aimed to evaluate the latest evidence of the sleep promoting properties of a selection of bioactive compounds (such as L-theanine and L-tryptophan) for the development of a functional beverage to improve sleep quality; and the effectiveness of traditional sleep promoting beverages (such as milk and chamomile). Overall, the bioactive compounds identified in this review, play essential roles in the synthesis and regulation of important neurotransmitters involved in the sleep-wake cycle. There is also significant potential for their inclusion in a number of functional beverages as the main ingredient on their own or in combination. Future studies should consider dosage; interactions with the beverage matrix, medications and other nutraceuticals; bioavailability during storage and following ingestion; as well as the sensory profile of the developed beverages, among others, when determining their effectiveness in a functional beverage to improve sleep quality.